The value of emotional intelligence for high performance coaching - Chan, J. T.; Mallett, C. J. (International Journal of Sports Science and Coaching, 2011)
Similar to an effective leader in business, a high-performance sports coach requires qualities beyond technical and tactical acumen, such as leadership and the ability to facilitate a functional leader-follower relationship. Underpinning this dynamic relationship that exists between the coach and athlete is a leader's acumen associated with emotional intelligence (EI). This article aims to highlight the utility of EI for high-performance sport coaches, and provide concrete examples as to how EI might enhance a coaches' ability to lead and direct the production of high-performance with their staff and athletes. First, a brief overview of the link between EI and leadership quality is presented. Second, Mayer and Salovey's (1997) four-branch model of EI (i.e., perceiving, using, understanding, and managing emotions) will be used as a framework for demonstrating how a coach may use such abilities to lead and produce high-performance.